Crystal structure prediction of rigid molecules. Issue 4 (3rd August 2016) - Elking, Dennis M.; Fusti-Molnar, Laszlo; Nichols, Anthony
Abstract : Methods and results are presented for the crystal structure prediction of rigid molecules using force fields. Abstract : A non‐polarizable force field based on atomic multipoles fit to reproduce experimental crystal properties and ab initio gas‐phase dimers is described. The Ewald method is used to calculate both long‐range electrostatic and 1/ r 6 dispersion energies of crystals. The dispersion energy of a crystal calculated by a cutoff method is shown to converge slowly to the exact Ewald result. A method for constraining space‐group symmetry during unit‐cell optimization is derived. Results for locally optimizing 4427 unit cells including volume, cell parameters, unit‐cell r.m.s.d. and CPU timings are given for both flexible and rigid molecule optimization. An algorithm for randomly generating rigid molecule crystals is described. Using the correct experimentally determined space group, the average and maximum number of random crystals needed to find the correct experimental structure is given for 2440 rigid single component crystals. The force field energy rank of the correct experimental structure is presented for the same set of 2440 rigid single component crystals assuming the correct space group. A complete crystal prediction is performed for two rigid molecules by searching over the 32 most probable space groups.